Gender-inclusive fintech and economic growth: The case of P2P lending in Indonesia - Salim, Dwi Fitrizal; Candraningtias, Widyadhana; Koerniawan, Koenta Adji; Isynuwardhana, Deannes (Edelweiss Applied Science and Technology, 2025)
This study investigates how financial performance indicators, gender-based user demographics, and the strategic role of fraud deterrence in peer-to-peer (P2P) lending fintech companies influence Indonesia’s economic growth. Using monthly data from May 2021 to December 2024, the study employs Ordinary Least Squares (OLS) regression to analyze the impact of variables such as Net Interest Margin, Company Scale, Interest Income Share, user gender composition, and governance-based deterrence practices on Indonesia’s GDP. The results show that Net Interest Margin, Company Scale, Interest Income Share, and female user participation significantly contribute to GDP growth. Furthermore, fraud deterrence emerges as a critical element in maintaining operational integrity and supporting long-term inclusivity in fintech development. Inclusive and well-governed fintech services—particularly those emphasizing gender engagement and institutional safeguards—play a vital role in promoting resilient and inclusive national economic growth. Policymakers and fintech practitioners should adopt gender-inclusive, fraud-sensitive lending models and governance improvements to maximize the sector’s macroeconomic contribution.